Is meaningful work a luxury? An interpretative phenomenological analysis on lower socioeconomic status workers' experience of meaningful work - Shim, Yerin, author; Dik, Bryan, advisor; Steger, Michael, committee member; Stallones, Lorann, committee member; Doe, Sue, committee member (Colorado State University. Libraries, 2016)
The growing empirical literature on meaningful work suggests that experiencing meaningful work is associated with many psychological benefits to the individual. However, very little is known about how lower socioeconomic status (LSES) workers experience meaningful work due to the lack of research with this population and assumption that pursuing meaningful work is a luxury. The present study sought to explore the experience of meaningful work among LSES workers through an interpretative phenomenological analysis (IPA) approach. Semi-structured interviews were conducted with eight LSES workers. Seven domains were constructed as a result of the data analysis: definitions of meaningful work, perception and psychological experience of meaningful work, internal conditions of meaningful work, external conditions of meaningful work, personal impact of meaningful work, strategies to enhance meaningfulness in work, and perspective on the relationship between meaningful work and SES. Participants defined meaningful work as similar to previous conceptualizations, perceived and experienced their current work as meaningful in diverse ways, and appeared to be generally positively impacted through meaningful work. Participants also identified direct and indirect conditions that support or hinder meaningfulness in their work and suggested strategies to enhance meaningfulness in their work. Finally, participants viewed meaningful work as an attainable psychological resource for LSES workers despite barriers.